SOCIO-POLITICAL IMPLICATIONS OF BODO MOVEMENT IN ASSAM - DAS, SANKAR (International Journal of Psychosocial Rehabilitation, 2020)
The movement which was started in 1920s by plain tribes with the demand of identity assertion is still continued in the region. The movement has gone through different phases to assume its present nature. The movement dominates the socio-political scenario of the Assam. It makes impact on socio political foundations of the state. Starting with the demand of identity assertion to demand of autonomy and later on with the statehood demand highly influence the state politics as well as common people of the region. The nature of Bodo movement has to be critically analyzed in order to understand the socio political reality of the region. The movement and its evolution to reach the present nature gives us a real picture of the society and prevailing condition in the region from different perspectives such as social, economic, political. So this paper tries to analyze the bodo movement from all these perspective and in addition tries to critically examine other dimensions such as peace, human rights, cooperation, administrative set up etc.